2021
DOI: 10.6000/2292-2598.2021.09.04.9
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis on the Impact of Gamification over Students’ Motivation

Abstract: Controversy surrounds the effectiveness of educational gamification on learners’ motivation to study. Prior papers attempting to summarize the available empirical evidence on the topic encompass too many additional domains like the academic performance so that the motivational point is discentrated. Hence, the current meta-analysis aimed to synthesize research findings limited to the clearly stated impact of gamification on higher education students’ academic motivation. Results from random effects proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Furthermore, 7 out of 10 studies found that gamification improves intrinsic motivation. Similar results have been found in a meta-analysis ofMamekova et al (2021). In the study the authors included 7 articles between 2011-2021.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, 7 out of 10 studies found that gamification improves intrinsic motivation. Similar results have been found in a meta-analysis ofMamekova et al (2021). In the study the authors included 7 articles between 2011-2021.…”
supporting
confidence: 78%
“…In general, the findings depicted in this paragraph suggest that the impact of gamification on motivation remains inconclusive, and incorporating game elements in learning environments can significantly enhance student engagement. A recent meta-analysis ofMamekova et al (2021) suggests that gamification can enhance motivation to learn, but only for about one-third of students.Nevertheless, as suggested byOrtiz-Rojas et al (2017), there is a need of assessing the motivation explicitly in the future studies in gamification in learning and education. One direction could be the motivation evaluation by using psychometrically validate measures like the Intrinsic Motivation Inventory (IMI)(Ryan, 1982) as suggested bySeaborn & Fels (2015) or other validated measures the authors can find in the following relevant papers(Mayer et al, 2007, Touré-Tillery & Fishbach, 2014.…”
mentioning
confidence: 99%
“…The common findings suggest that gamification or game-based learning improves learning outcomes (Kim & Castelli, 2021;Mazeas et al, 2022). Researchers argue that game-based learning makes students more enthusiastic and happier (Mazeas et al, 2022) and helps them understand contexts (Kim & Castelli, 2021), thereby enhancing learning motivation (Mamekova et al, 2021) and improving learning outcomes (Fadhli et al, 2020). A meta-analysis study specifically focuses on the relationship between gamification and STEM learning but only concentrates on virtual games with data from 2010 to 2020 (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed results also come from studies on one of the most often cited reasons for gamifying learning environments: motivation. Some studies show that gamification enhances motivation in educational context (Sailer and Homner, 2020;Oliveira Jordao do Amaral and Kang, 2021;Mula-Falcón et al, 2022), while others have found no increase in student motivation after implementing gamification (Domínguez et al, 2013;Hanus and Fox, 2015;Faust, 2021;Tanirbergenovna et al, 2021). Variability of the effects that elements of gamification have-or not have-on student learning reinforces the need to keep exploring different ways to design and implement game-design elements in learning environments in ways that will facilitate student learning.…”
Section: Introductionmentioning
confidence: 99%